Application of MBJ-Neutrosophic in BRK-Algebra - Alshehri, Halimah; Almuhaimeed, Areej (Communications in Mathematics and Applications, 2025)
This paper introduces the concept of MBJ-neutrosophic ideals and subalgrbras in BRK-algebras. We study various properties regarding these concepts. Also, a relationship between MBJ-neutrosophic ideals and MBJ-neutrosophic subalgrbras is presented. Moreover,  various characterisations for MBJ-neutrosophic ideals are proved.
Keywords: MBJ-neutrosophic; BRK-algebra; Ideal; Subalgebra